Risk factors for complications and readmission after operative fixation of pediatric femur fractures. (August 2015) - Momaya, Amit; Baker, Dustin; Gilbert, Shawn; Ponce, Brent
Purpose: Operative fixation of pediatric femur fractures with intramedullary implants has grown in popularity in recent decades. However, risk factors for short-term adverse events and readmission have not been well studied. Methods: Pediatric patients who underwent intramedullary nailing of a femur fracture between 2012 and 2013 were identified from the American College of Surgeons National Surgical Quality Improvement Program database. Risk factors for any adverse event (AAE) and readmission after intramedullary nailing were evaluated using univariate and multivariate analysis. Results: A total of 522 pediatric patients who underwent intramedullary nailing of the femur during the study period were identified. The mean age of this patient cohort was 10.2 ± 3.8 years. Review of the cases revealed that 18 (3.4 %) patients had AAE and that 20 (3.8 %) patients were readmitted, of whom 13 (2.5 %) underwent a reoperation. Independent risk factors for AAE were a cardiac comorbidity [odds ratio (OR) 12.7, 95 % confidence interval (CI) 1.5, 103.7], open fracture (OR 10.2, 95 % CI 1.4, 74.4), and prolonged operative time (OR 17.5, 95 % CI 6.1, 50.5). Independent risk factors for readmission were a central nervous system disorder (OR 4.5, 95 % CI 1.3, 16.2) and a seizure disorder (OR 4.9, 95 % CI 1.0, 23.5). Conclusions: The results of the multivariate analysis suggest that cardiac comorbidities, open fractures, and prolonged operative time increase the risk for AAE and that central nervous system disorders and seizure disorders may increase the risk for readmission. Surgeons should be aware of these risk factors and counsel the families of pediatric patients who undergo intramedullary nailing of femur fractures.